Peran Teori Akuntansi Terhadap Sistem Pelaporan Keuangan Pada PT. Abdi Budi Mulia (ABM) - Sri Anggraini; Maharani Maharani; Rahmad Pardosi (Akuntansi, 2024)
This article discusses the role of accounting theory in the financial reporting system at PT companies. Abdi Budi Mulia. Accounting theory has an important role in the development of accounting systems and financial reporting in companies. This research uses a qualitative descriptive method by conducting a case study at PT. Abdi Budi Mulia. The research results show that the company has implemented accounting theory in its financial reporting system. However, there are several challenges and obstacles that stand in the way of implementing an accounting system, such as changes in regulations, limited human resources, use of technology, limited time and costs, as well as difficulties in processing data. Therefore, companies must pay attention to these factors in developing a better and more integrated accounting system. In this article, the author also discusses the influence of accounting history in Europe, America and Indonesia on the development of the accounting system in Indonesia, as well as the challenges and obstacles that may be faced in implementing the accounting system at PT. Abdi Budi Mulia. It is hoped that this article can provide insight and a better understanding of the role of accounting theory in the development of accounting systems and financial reporting in companies.